2017
DOI: 10.1007/s11060-017-2434-8
|View full text |Cite
|
Sign up to set email alerts
|

CDC20 with malignant progression and poor prognosis of astrocytoma revealed by analysis on gene expression

Abstract: The malignant transformation of astrocytoma may result from the accumulation of multiple genetic alterations. Current research shows that diffuse astrocytoma (AIIs, WHO grade II) is inherently predisposed to recur locally, and to spontaneously progress to anaplastic astrocytoma (AAIIIs, WHO grade III) and eventually secondary glioblastoma (sGBMIVs, WHO grade IV). The aim of the study was to identify and validate the important gene(s) associated with malignant progression and poor prognosis of astrocytoma. Aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Cell migration of the PANC-1 cells treated with PTE (30 and 60 µg/ml) or PPAC (30 and 60 µM) was assessed in Transwell chambers according to an established method (29). The PANC-1 cells (0.2x10 6 ) suspended in serum-free medium were added to the upper chamber of an insert, and the insert was placed in a 24-well plate containing medium with 10% FBS. The migration assays were performed for 24 h at 37˚C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell migration of the PANC-1 cells treated with PTE (30 and 60 µg/ml) or PPAC (30 and 60 µM) was assessed in Transwell chambers according to an established method (29). The PANC-1 cells (0.2x10 6 ) suspended in serum-free medium were added to the upper chamber of an insert, and the insert was placed in a 24-well plate containing medium with 10% FBS. The migration assays were performed for 24 h at 37˚C.…”
Section: Methodsmentioning
confidence: 99%
“…It activates the anaphase-promoting complex/cyclosome, thus modulating mitotic exit through the proteasomal degradation of proteins (2)(3)(4). Aberrant expression of CDC20 is associated with malignant progression and poor prognosis in various types of cancer, including pancreatic ductal adenocarcinoma, gastric cancer, urothelial bladder cancer, astrocytoma, hepatocellular carcinoma, lung adenocarcinoma and oral squamous cell carcinoma (5)(6)(7)(8)(9)(10)(11). In addition, there is a significant correlation between a high expression of CDC20 and advanced tumor stage in carcinoma of the breast, colon, endometrium and prostate (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The latter tumors were further divided on histopathological grounds into three grades of malignancy associated with distinct median survival rates (range: from 1 to > 10 years) 5,6 : WHO grade-II diffuse astrocytoma (DA), WHO grade-III anaplastic astrocytoma (AA) and WHO grade-IV glioblastoma (GBM). Of note, DA might evolve to AA, and AA might transform to GBM 7,8 . Because of this, GBM is further subdivided into primary de novo GBM (pGBM) and secondary GBM (sGBM) resulting from progression of a prior lower grade astrocytic tumor (e.g.…”
mentioning
confidence: 99%
“…Because of this, GBM is further subdivided into primary de novo GBM (pGBM) and secondary GBM (sGBM) resulting from progression of a prior lower grade astrocytic tumor (e.g. AA) 7 .…”
mentioning
confidence: 99%
“…Our study also highlights the utility of small-molecule inhibition of APC/C CDH1/CDC20 as a therapeutic strategy to target CSCs in GBM. Elevated CDC20 expression has previously been correlated with high grade glioma, as well as poor patient prognosis by a number of groups (54)(55)(56)(57). We and others have shown that CDC20 is higher in CSCs over NSTCs and, more recently, RNAi has validated CDC20 as a critical modulator of the CSC phenotype (13)(14)(15).…”
Section: Discussionmentioning
confidence: 61%